Pemberdayaan Pemuda Berbasis Masjid di Desa Waru Jaya, Parung, Bogor, Jawa Barat - Rahmatusadiyah, Rahmatusadiyah (Tazkia Islamic University College, 2024)
The Youth of the Mosque is an important organization for Muslims in Indonesia, playing a role in prospering the mosque through various religious, educational, and skill-building activities. In Waru Jaya Village, the PPID organization, together with IRMAS and IRMUS, in collaboration with Karang Taruna, runs various youth empowerment programs. These activities include regular training, weekly recitations, and annual events such as Tabligh Akbar and Sanlat. Despite facing various challenges, such as limited funding and lack of participation, strategic steps have been taken to address them, such as expanding donor relations and increasing youth involvement. Evaluations show success in the implementation of routine and social activities, although some programs were not implemented due to external obstacles. In conclusion, mosque-based youth empowerment in Waru Jaya Village has successfully increased skills and social involvement, although improvements in funding and participation are needed.